2018
DOI: 10.3382/ps/pey005
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality traits in the Greater rhea (Rhea americana) as influenced by muscle, sex and age

Abstract: Meat from the Greater rhea (Rhea americana) could compete with traditional red meats, diversifying the market of protein products of animal origin. The meat from 32 rheas was used to study quality aspects and this included ultimate pH (pHu), color, water-holding capacity (WHC%), cooking loss (CL%) and tenderness. The muscles sampled were the Gastrocnemius pars externa, Iliofibularis and Obturatorius medialis from both sexes at multiple ages (10, 12, 14, 16 months). Age at slaughter affected WHC%, CL%, and colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…pH is an important index of muscle quality and can affect muscle color and tethering power. The lower the drip loss, the higher the turgidity and tenderness of the muscle ( Zhang et al., 2015 ; Bernad et al., 2018 ). Tang et al.…”
Section: Discussionmentioning
confidence: 99%
“…pH is an important index of muscle quality and can affect muscle color and tethering power. The lower the drip loss, the higher the turgidity and tenderness of the muscle ( Zhang et al., 2015 ; Bernad et al., 2018 ). Tang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the muscle is usually assessed by color, tethering power, and shear force (56). Wu et al (57) showed that 24 h after slaughter, high-stocking density (18.6 birds/m 2 ) significantly increased L* and decreased a* values of breast muscle in broilers compared to low stocking density (12.9 birds/m 2 ) and also resulted in higher drip losses.…”
Section: Discussionmentioning
confidence: 99%
“…The supply of cold water as against tap water influenced various physiological variables since it decreased the tonic immobility, body temperature, and blood levels of cholesterol, AST, and ALT, whereas, it increased the globulin, glucose, and total antioxidant capacity of the birds ( 124 ). Importantly, the provision of wet feed and cold water during high summer temperatures improved the body weight and body weight gain of ducks ( 124 ).…”
Section: Water Managementmentioning
confidence: 99%
“…The supply of cold water as against tap water influenced various physiological variables since it decreased the tonic immobility, body temperature, and blood levels of cholesterol, AST, and ALT, whereas, it increased the globulin, glucose, and total antioxidant capacity of the birds ( 124 ). Importantly, the provision of wet feed and cold water during high summer temperatures improved the body weight and body weight gain of ducks ( 124 ). Supplying cold water with afternoon feed withdrawal was found to decrease body temperature and tonic immobility, whereas, it improved the production performance, blood composition, and the total antioxidant capacity of Muscovy ducklings during summer heat ( 125 ).…”
Section: Water Managementmentioning
confidence: 99%